Bazi Bushen capsule improves the deterioration of the intestinal barrier function by inhibiting NLRP3 inflammasome-mediated pyroptosis through microbiota-gut-brain axis - Zhang, Shixiong; Li, Mengnan; Chang, Liping; Mao, Xinjing; Jiang, Yuning; Shen, Xiaogang; Niu, Kunxu; Lu, Xuan; Zhang, Runtao; Song, Yahui; Ma, Kun; Li, Hongrong; et al. (Frontiers in Microbiology, 2024)
Purpose: The senescence-accelerated prone mouse 8 (SAMP8) is a widely used model for accelerating aging, especially in central aging. Mounting evidence indicates that the microbiota-gut-brain axis may be involved in the pathogenesis and progression of central aging-related diseases. This study aims to investigate whether Bazi Bushen capsule (BZBS) attenuates the deterioration of the intestinal function in the central aging animal model. Methods: In our study, the SAMP8 mice were randomly divided into the model group, the BZ-low group (0.5 g/kg/d BZBS), the BZ-high group (1 g/kg/d BZBS) and the RAPA group (2 mg/kg/d rapamycin). Age-matched SAMR1 mice were used as the control group. Next, cognitive function was detected through Nissl staining and two-photon microscopy. The gut microbiota composition of fecal samples was analyzed by 16S rRNA gene sequencing. The Ileum tissue morphology was observed by hematoxylin-eosin staining, and the intestinal barrier function was observed by immunofluorescence. The expression of senescence-associated secretory phenotype (SASP) factors, including P53, TNF-α, NF-κB, IL-4, IL-6, and IL-10 was measured by real-time quantitative PCR. Macrophage infiltration and the proliferation and differentiation of intestinal cells were assessed by immunohistochemistry. We also detected the inflammasome and pyroptosis levels in ileum tissue by western blotting. Results: BZBS improved the cognitive function and neuronal density of SAMP8 mice. BZBS also restored the intestinal villus structure and barrier function, which were damaged in SAMP8 mice. BZBS reduced the expression of SASP factors and the infiltration of macrophages in the ileum tissues, indicating a lower level of inflammation. BZBS enhanced the proliferation and differentiation of intestinal cells, which are essential for maintaining intestinal homeostasis. BZBS modulated the gut microbiota composition, by which BZBS inhibited the activation of inflammasomes and pyroptosis in the intestine. Conclusion: BZBS could restore the dysbiosis of the gut microbiota and prevent the deterioration of intestinal barrier function by inhibiting NLRP3 inflammasome-mediated pyroptosis. These results suggested that BZBS attenuated the cognitive aging of SAMP8 mice, at least partially, by targeting the microbiota-gut-brain axis.